A Study of Investigators’ Trust and Satisfaction toward Crime Scene Examination Work of the Provincial Forensic Science Office, Phichit Province - สุวรรณชื่น, ภุชงค์ (การประชุมวิชาการระดับชาติและนานาชาติ เบญจมิตรวิชาการ ครั้งที่ 16, 2026)
The objectives of this research were: 1) to study the level of investigators’ trust toward the crime scene investigation work of the Phichit Provincial Forensic Science Division, 2) to study the level of investigators’ satisfaction with the crime scene investigation work of the Phichit Provincial Forensic Science Division, and 3) to examine problems and obstacles in the collaboration between investigators and forensic officers. This study employed a quantitative research approach. The sample consisted of 67 investigators working in 17 police stations across Phichit Province. The research instrument was a questionnaire composed of two parts: a trust questionnaire with a reliability coefficient of 0.92 and a satisfaction questionnaire with a reliability coefficient of 0.88. The data were analyzed using frequency, mean, and standard deviation.          The findings revealed that the overall levels of investigators’ trust and satisfaction toward the crime scene investigation work were at the highest level. Considering each aspect, the highest mean score of trust was found in the operational performance aspect, followed by knowledge and competence. For satisfaction, the personnel service aspect had the highest level, followed by facilities, service procedures, and service time, respectively. The main problems and obstacles in the collaboration between investigators and forensic officers were delays in urgent communications, a lack of facilities at evidence transfer points, and delays in the delivery of forensic examination reports. The study suggested that an effective communication channel, such as a Line group between investigators and forensic officers, should be established. Moreover, the number of forensic officers should be increased to meet the workload, and the scope of forensic examinations should be expanded to enhance investigators’ trust and satisfaction toward the forensic science services.